Peptide Analysis from Soil Actinomycetes Exhibiting Antimicrobial and Antiproliferative Activities - Kalyani, Manjula Ishwara (International Journal of Pharmaceutical & Biological Archive, 2018)
Actinomycetes are considered a potential group of microorganisms capable of producing bioactivemolecules. In the present study, the actinomycetes species belonging to the genus Thermoactinomycetes,Micromonospora and predominantly Streptomyces were isolated from maize rhizosphere soil and fromcompost soil. With anticipating the isolation of potential antimicrobial peptides from the actinomycetesisolates, the isolates were subjected for total protein extraction after growing them in starch casein nitratemedia. The antimicrobial peptides are low molecular weight peptides attacking the cell membrane byionic interactions, thus disrupting membrane integrity of invading pathogens or the abnormal cells suchas cancer cells. The peptides obtained from actinomycetes were analyzed by SDS-PAGE technique aftertheir salt precipitation and dialysis. The total peptides were checked for antimicrobial activity against thebacteria Pseudomonas sp, Enterobacter sp, Klebsiella sp, Streptococcus sp, Escherichia coli andStaphylococcus aureus. The peptides obtained from Streptomyces predominantly showed effectiveantibacterial activities. The compost isolated actinomycetes mainly identified belonging toThermoactinomycetes, Micromonospora and Streptomyces also showed antibacterial activity but showedgood antiproliferative effect against the proliferative yeast cultured cell lines. The morphological featuresof actinomycetes were characterized by gram staining, acid fast staining and slide culture techniques.